EFEKTIFITAS BUDAYA ISLAMI DALAM MENUMBUHKAN KARAKTER SISWA DI SMA MUHAMMADIYAH 1 TAMAN - Agus Ishom; Taufikurrohma Taufikurrohma; Istikomah Istikomah (Universitas Muhammadiyah Surakarta, 2020)
This paper discusses the effectiveness of Islamic Culture in Growing Student Character. Schools must instill the main values early on students so that later they can practice these main values in real life in society, whatever the profession School culture related to certain characters is not static, but must continue to be developed by the demands of the times and society and information-technology advancements. Schools must be firm in showing what characters they want to develop so that the user community can choose and even control the achievement of the inculcation of these characters. Schools should be able to invite all parties (including stakeholders) to work together to realize the birth of a school culture that focuses on certain characters. This research is qualitative-descriptive research which is expected to be able to uncover various information with a careful and meaningful description-analysis. Sources of data in this study include the principal, student waka, Al-Islam teacher, and Kemuhammadiyah. Data collection is done by interview, observation, and documentation. As for the data analysis technique through the stages of data reduction, data presentation, and data analysis. The results of the research include (a) strategies to grow student character (2) Effectiveness of Islamic Culture in growing residual character